Comments: totally endoscopic (VATS) first rib resection for thoracic outlet syndrome - Povlsen, Bo (Journal of Thoracic Disease, 2016)
Dear Editor, It is an honour to be asked to write a comment on the paper by George et al. (1) as I have a particular interest in the treatment of Thoracic Outlet Syndrome as I have been the main author on the most recent Cochrane review on Treatment for thoracic outlet syndrome (2).